CRIMINOLOGY AND POLICY: AN ANALYSIS OF THE EFFECTIVENESS OF RESTORATIVE JUSTICE APPROACHES ON PRISON OVERCROWDING IN INDONESIA - Nathaniel Ramos; Carlos Fernandez; Catherine Li (Yayasan Adra Karima Hubbi, 2026)
Indonesia faces a severe prison overcrowding crisis, with national overcapacity rates often exceeding 200%. Restorative Justice (RJ) has been formally adopted as a primary policy response, yet its empirical effectiveness as a large-scale diversionary tool to mitigate this crisis remains unverified. This study aimed to quantitatively analyze the effectiveness of RJ implementation in reducing new prison admissions and slowing the growth of total carceral populations in Indonesian jurisdictions. A quasi-experimental, comparative interrupted time-series (ITS) design was employed. Aggregate panel data from 40 matched jurisdictions (20 High-RJ implementation, 20 Low-RJ control) were analyzed over a 120-month period (2015-2024). A fixed-effects regression model was used to isolate the policy’s impact. -Implementation RJ jurisdictions showed significantly slower carceral population growth (9.1%) compared to Low-Implementation controls (38.4%). The regression analysis confirmed a robust, negative relationship between RJ diversions and new prison admissions (B = -0.81, p < .001), demonstrating a near one-to-one substitution effect. The findings provide strong quantitative evidence that RJ is an effective, data-driven policy for mitigating prison overcrowding. The crisis persists not from a lack of a solution, but from a failure of consistent implementation, which must be standardized to realize its full potential.